نماذج تقدير الزحف والانكماش للبيتون العادي والبيتون عالي الأداء مفهوم لطريقة موحدة من نماذج الكودات - شديد إدوارد; محفوظ نهى (Latakia University Journal -Engineering Sciences Series, 2019)
يبدأ البحث بعرض المتطلبات الواجب توفرها في أي تمثيل رياضي لخصائص الزحف والانكماش، ثم يلخص خصائص الزحف والانكماش للبيتون عالي الأداء ويقارنها بالبيتون عادي المقاومة. ويبين البحث أن التنبؤ بالزحف و الانكماش لكل من البيتون عالي الأداء والبيتون عادي المقاومة يمكن أن يتم باستخدام أسلوب واحد قريب من النموذج الرياضي الذي تبنته الجمعية الأوربية للبيتون و الاتحاد الدولي لسبق الإجهاد (CEB - FIP) في عام 1990 في حال اعتماد بعض التعديل و التوسعة لمجال الصيغ الأصلية. ولقد تمت معايرة النموذج الرياضي المطور اعتماداً على المعطيات المتوفرة في قاعدة RILEM للمعلومات عن الزحف والانكماش< ويعرض البحث دراسة إحصائية عن مدى الفرق في مجالات تطبيق النموذج الرياضي الجديد. ولقد تمت صياغة النموذج الرياضي المعتمد ضمن برنامج حاسب يقوم بحساب تشوهات الزحف والانكماش مع الزمن آخذاً بعين الاعتبار جميع المتغيرات التي اعتمدها النموذج الرياضي, ويمكن من خلال هذا البرنامج الوصول إلى منحنيات تشوه مع الزمن لأي حالة مفروضة, ويشكل بذلك أداة تحليلية فعالة ومرنة لمقارنة النتائج التجريبية التي يتم الوصول إليها. The paper starts by listing the requirements needed in any mathematical modeling of the characteristics of creep and shrinkage in concrete, followed by describing the characteristics of creep and shrinkage in high performance concrete (HPC) and comparing these with normal strength (NSC). The paper shows that creep of shrinkage for both HPC and NSC can be predicted using a unified method, close to the mathematical model presented by CEB-FIP in 1990, by simply introducing some modifications and extending the range of formulae used. The developed mathematical model has been calibrated against an extensive data base RILEM on creep and shrinkage. The paper includes a statistical study of applicability of the model and the extent of variation upon its application. The selected mathematical model was incorporated into a computer program that calculates creep and shrinkage deformations over time, taking into considerations all the variables that went into the mathematical model. The program enables the consideration of time deformation curves for any given situation, representing an effective and flexible analytical tool to compare the experimental results measured.